Land take in environmental assessments: Recent advances and persisting challenges in selected EU countries. (December 2021) - Schatz, Eva-Maria; Bovet, Jana; Lieder, Sebastian; Schroeter-Schlaack, Christoph; Strunz, Sebastian; Marquard, Elisabeth
Abstract: In this paper, we present results from an in-depth questionnaire survey, in which experts from ten EU Member States and the UK assessed the progress towards the EU's 'no net land take by 2050' target within their countries. The survey focused in particular on how Directive 2014/52/EU has been implemented at national level. The revised directive stipulates for the first time explicitly that Environmental Impact Assessments (EIAs) should consider 'land' in addition to 'soil', thereby opening up the possibility that EIAs will play a more significant role in curbing land take. However, the results from our survey suggest that the impact from including the factor 'land' in EIAs has remained limited so far. Against this background, we discuss likely reasons for this observation, highlight persistent challenges for tackling land take effectively, and reflect on options to mitigate barriers on the way toward the European 'no net land take by 2050' target. Highlights: Limited practical impact of the EIA factor 'land' so far in studied EU countries. Distinction of 'land' vs. 'soil' in practice mostly based on quantity vs. quality. Clarifications, useful indicators and links to existing land take targets needed.